Implementation Plan in Response to The Board : Endorsed Recommendations from The IEO Evaluation Report on Growth and Adjustment in IMF - Supported Programs. (Policy Papers; Policy Paper, 2022)
This management implementation plan (MIP) proposes actions in response to the Independent Evaluation Office (IEO)'s report on growth and adjustment in IMF-supported programs. The full implementation of the MIP package will help ensure that, at a time when many countries face strong headwinds, IMF-supported programs not only deliver necessary adjustment to address balance of payments needs but also pay greater attention to their growth effects. While the policy-related deliverables are already incorporated into current departmental work plans and budgets, the operational implementation of these recommendations may require mobilizing additional resources.